Diagnóstico da atividade pesqueira do Arquipélago de Fernando de Noronha/PE: sugestões para o manejo - Zeineddine, Gabriela Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Artisanal fishing exerts significant influence in several locations in Brazil, including the Northeast and the Archipelago of Fernando de Noronha-PE. Despite the worldwide social and economic importance of fishing being imminent, this activity is also a major source of disturbances in the marine environment, making fisheries management and planning actions essential for resource conservation and activity sustainability. Due to the lack of existing data regarding fishing categories developed in Fernando de Noronha, as well as current fishing statistics that support its planning, this work aims to diagnose current fishing practices and suggest management alternatives based on the local fishing reality, with ways to make conservation and local fisheries management compatible. The data for this research were collected within the scope of fishing management carried out by ICMBio Noronha through fishing monitoring, fishing monitoring plans, and participatory fishing diagnosis meetings held with the management body and the local community. Currently, there are 94 fishermen in Fernando de Noronha, of which 35 carry out fishing activities on the beaches and 59 on boats. The fishing fleet is composed of 46 vessels, of which 27 carry out fishing activities, fishing tourism, and tours, and 19 are exclusively for fishing. Local fishing activity falls into three fishing categories: professional fishing, subsistence fishing, and amateur fishing. There is also fishing tourism, a tourist activity that interfaces between professional and amateur fishing. Despite the fishing fleet being small and fishing being restrictive in terms of richness, it was possible to observe seasonal patterns in catches, with autumn being the most productive season due to climatic factors. The geographical issues of fishing spots also have a direct influence on the composition and abundance of fishing production, demonstrating different behaviors for small and medium-sized vessels, which occupy spaces more or less distant from the island of Fernando de Noronha. The main current social need is the valorization of traditional fishing and the reestablishment of its pillars, such as strengthening the fishing class, unity among fishermen, and incentives for awareness programs and appreciation of fish and traditional culture, as well as active participation of the fishing community in management decision making. This study is expected to support decision-making for island fisheries management, as well as new research related to the topic.

A pesca artesanal exerce grande influência em várias localidades do Brasil, dentre elas o nordeste e o Arquipélago de Fernando de Noronha-PE. Ainda que a importância social e econômica da pesca seja mundialmente iminente, essa atividade também é uma grande fonte de impactos no ambiente marinho, o que torna a gestão e ações de ordenamento pesqueiro indispensáveis para a conservação dos recursos e sustentabilidade da atividade. Devido à lacuna de dados existentes a respeito das categorias de pesca desenvolvidas em Fernando de Noronha, bem como de estatísticas pesqueiras atuais que subsidiem o seu ordenamento, este trabalho objetiva diagnosticar a pesca da atualidade e sugerir alternativas de gestão baseadas na realidade pesqueira local, com vias de compatibilizar a conservação e gestão pesqueira local. Os dados desta pesquisa foram coletados no âmbito da gestão pesqueira realizada pelo ICMBio Noronha através do monitoramento pesqueiro, embarques para acompanhamento da pesca, e de reuniões de diagnóstico participativo da pesca realizadas com o órgão gestor e comunidade local. Atualmente existem 94 pescadores em Fernando de Noronha, dos quais 35 realizam a atividade pesqueira nas praias e 59 em barcos, a frota pesqueira é composta por 46 embarcações, dos quais 27 desenvolvem atividades de pesca, turismo de pesca e passeios e, 19 são exclusivamente de pesca. A atividade pesqueira local está inserida em três categorias de pesca: a pesca profissional, a pesca de subsistência, e a pesca amadora. Existe também o turismo de pesca, uma atividade turística que faz interface entre a pesca profissional e a amadora. Apesar da frota pesqueira ser pequena e a pesca ser restritiva em relação à riqueza, foi possível observar padrões sazonais nas capturas, sendo o outono a estação mais produtiva devido aos fatores climáticos. As questões geográficas dos pontos de pesca também possuem influência direta na composição e abundâncias da produção pesqueira, demonstrando comportamentos distintos para embarcações de pequeno e médio porte, que ocupam espaços diferenciados em relação à ilha de Fernando de Noronha. A principal necessidade social atual é a valorização da pesca local e o restabelecimento dos seus pilares, como: fortalecimento da classe pesqueira, união entre os pescadores e incentivos para programas de conscientização e valorização do pescado e da cultura associada à atividade, bem como participação ativa da comunidade pesqueira nas tomadas de decisões da gestão. Espera-se com este estudo, subsidiar tomadas de decisões para a gestão pesqueira insular, bem como novas pesquisas relacionadas ao tema.
Diagnóstico de la actividad pesquera en el Archipiélago de Fernando de Noronha, Pernambuco: sugerencias para la gestión
Keywords: Pesca; Recursos pesqueiros; Unidades de Conservação; Gestão Ambiental